PENGARUH UKURAN DIAMETER PIPA OUTLET FOAM GENERATOR TERHADAP KUAT TEKAN DAN SERAPAN AIR BATA RINGAN JENIS CLC - Bella, Rosmiyati A.; Sinlae, Astryana M.; Pah, Jusuf J. S. (Jurnal Teknik Sipil, 2016)
The power of Cellular Lightweight Concrete is influenced by the size of its pores. If the Lightweight Concrete’s pore is larger, then the compressive strength is smaller and the uptake of water produced is greater. This is caused by the using of the outlet pipe diameter that is greater cause cavities in the foam produced even greater. That foam occupy cubes of concrete’ space and generate pores that are large on the Lightweight Concrete, causing its compressive strength are small and water’s absorption is large if it is compared to the diameter of the outlet pipe is smaller. The test results in the laboratory is the compressive strength of Cellular Lightweight Concrete in 14 days amounted to 2.148 MPa, 2.074 MPa, 1.926 MPa and 1.852 MPa on the variation of ½ inch, 1 inch, 1 ½ inch and 2 inches diameter. In 28 days, it amounted to 2,667 MPa, 2,593 MPa, 2,444 MPa, dan 2,296 MPa with same diameters. In 42 days, it amounted to 2,815 MPa, 2,667 MPa, 2, 519 MPa, dan 2,444 MPa on diameter of 0,5 inch, 1 inch, 1,5 inch, and 2 inches. In 56 days, it amounted to 2,889 MPa, 2,741 MPa, 2,593 MPa, and 2,519 MPa with same diameters. At the age of 56 days, the average value of water absorption of the CLC with outlet foam generator of diameter of 0.5 inches amounted to 13.554%. Whereas on 1-inch increase to 15.268%. The size of 1.5 inches increased to 17.163% and the size of 2 ins by 19.463%.